Drosophila melanogaster experimental model to test new antimicrobials: a methodological approach - Vidal, Maria; Arch, Marta; Fuentes, Esther; Cardona, Pere-Joan (Frontiers in Microbiology, 2024)
Given the increasing concern about antimicrobial resistance among the microorganisms that cause infections in our society, there is an urgent need for new drug discovery. Currently, this process involves testing many low-quality compounds, resulting from the in vivo testing, on mammal models, which not only wastes time, resources, and money, but also raises ethical questions. In this review, we have discussed the potential of D. melanogaster as an intermediary experimental model in this drug discovery timeline. We have tackled the topic from a methodological perspective, providing recommendations regarding the range of drug concentrations to test based on the mechanism of action of each compound; how to treat D. melanogaster, how to monitor that treatment, and what parameters we should consider when designing a drug screening protocol to maximize the study’s benefits. We also discuss the necessary improvements needed to establish the D. melanogaster model of infection as a standard technique in the drug screening process. Overall, D. melanogaster has been demonstrated to be a manageable model for studying broad-spectrum infection treatment. It allows us to obtain valuable information in a cost-effective manner, which can improve the drug screening process and provide insights into our current major concern. This approach is also in line with the 3R policy in biomedical research, in particular on the replacement and reduce the use of vertebrates in preclinical development.